Sustainable Innovations in Steam Generation for Food Sterilization Processes: A Review - Atheer Abdul Amir Al-Mtury; Sabah Malik Al-Shatty; Asaad R. Al-Hilphy; Muhammad Faisal Manzoor (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
The current review aimed to identify the recent developments in sustainable steam generation and its applications in food sterilization. Fuel, gas, and coal boilers are the traditional methods for producing steam. Recently, innovative methods of steam generation include electrodes, solar, natural gas, nano-electric, biogas, biomethane boilers, and sustainable steam generation through heat pump (heat pump is an energy-efficient device that transfers heat from one location to another, typically using electricity). The calories in the 100% saturated steam are higher than steam saturation by 95%. The solar parabolic dish system includes biaxial tracking mechanism that ensures increased efficiency and useful energy production due to the increased radiation. Electrode boilers generate steam using electric current, offering simplicity, reliability, and efficiency. Nano-electric boiler boasts a high-power density, minimal carbon emissions, great physical stability, and high-power factor and electric conversion efficiency. The efficiency of natural gas, biogas and biomethane boilers ranges from 94% to 95% with an economizer. The air-source heat pump boiler provides stable system output with high energy efficiency, generating steam at temperatures exceeding 120°C. Water content below 0.01% mass is necessary for steam purity to prevent overheating. The thermal treatment of canned food should reduce bacteria levels by 12 log cycles in low-acid foods to meet safety limits. The container contains 1 spores for Clostridium botulinum for thermal treatment (sterilization) at 121°C. The process involves sterilizing materials at 121°C for 15 min, killing most heat-resistant microorganisms. The innovative steam sterilization methods aim to advance industrial uses that fulfill net-zero emissions and sustainable development goals (SDG).